2004
DOI: 10.1038/ni1093
|View full text |Cite
|
Sign up to set email alerts
|

RabGEF1 is a negative regulator of mast cell activation and skin inflammation

Abstract: Mast cell activation induced by aggregation of Fc epsilon RI receptors with immunoglobulin E and antigen is mediated through the activation of multiple protein kinase cascades. Here we report that the regulatory protein RabGEF1 bound to Ras and negatively regulated Ras activation and its 'downstream' effector pathways in Fc epsilon RI-dependent mast cell activation. RabGEF1-deficient mast cells showed enhanced degranulation and release of lipid mediators and cytokines in response to Fc epsilon RI aggregation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
80
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 49 publications
7
80
2
Order By: Relevance
“…of Rabex-5 in mast cells, suggesting that the phenotype of Rabex-5-deficient mice might reflect, at least in part, defective mast cell function (4,25,26). Here, we have reported that Rabex-5 is a critical negative regulator of type 1 IFN production.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…of Rabex-5 in mast cells, suggesting that the phenotype of Rabex-5-deficient mice might reflect, at least in part, defective mast cell function (4,25,26). Here, we have reported that Rabex-5 is a critical negative regulator of type 1 IFN production.…”
Section: Discussionmentioning
confidence: 72%
“…Here, we identify Rabex-5 as an IMiD target molecule. The phenotype of Rabex-5-deficient mice, which spontaneously develop a fatal inflammatory skin disorder (4), taken together with our observations here, strongly suggests the involvement of Rabex-5 in mediating IMiD properties.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…A coiled-coil domain downstream of the GEF domain may mediate the binding to Rabaptin-5, as shown in a yeast two-hybrid assay , whereas a Zn 2ϩ finger (ZnF) domain at the N terminus is shown to bind ubiquitin (Lee et al, 2006;Mattera et al, 2006;Penengo et al, 2006). Recently, Rabex-5 (also called Rab-GEF1) knockout mice have been generated, and they die early and develop severe skin inflammation (Tam et al, 2004). Mast cells isolated from these Rabex-5-deficient mice show enhanced stem cell factor/c-Kit-mediated signal transduction and biological responses (Kalesnikoff et al, 2006).…”
Section: Introductionmentioning
confidence: 99%